(untitled) (Educational Knowledge, 2025)
This paper examines the integration of artificial intelligence (AI) in education by analyzing documents published between 2020 and 2023 in the Scopus and Web of Science databases. The predominance of academic articles reveals a strong commitment to in-depth analysis of AI in education. Brazil, Spain, and Peru lead in publication output, reflecting the global relevance of the topic. While “Educational Technology” was the main search term, “AI in Teaching” has also gained importance, indicating a steady increase in literature on the subject. A balanced gender representation among authors was observed. However, the study identifies methodological limitations and emphasizes the need for future research involving broader samples and more advanced statistical techniques to better understand the relationship between AI and education.